Sex differences of molecular mechanisms of insulin sensitivity in young and adult C57BL/6J mice - T. V. Yakovleva; A. Yu. Kazantseva; E. N. Makarova; N. M. Bazhan (Вавиловский журнал генетики и селекции)
Reduced insulin sensitivity plays an important role in the pathogenesis of type II diabetes. There are sex differences in the development of metabolic disorders. The aim of this work was to investigate the insulin signal transduction gene expression in mice of different sex and age. Male and female C57BL/6J mice were used in our studies. Gene expression was assayed by RT-PCR. It was shown that insulin sensitivity in females was higher than in males regardless of age because the level of glucose in blood plasma of females does not differ from that in males, whereas female insulin levels were lower than male insulin levels. Female glucose tolerance increased with age, and glucose tolerance was higher in females than in males at the age of 30 weeks. It was shown that sex and age affect the expressions of insulin signal transduction genes. It was shown that there are sex differences in the levels of mRNA Pik3cd in the liver, in the levels of mRNA Irs1 in the muscle, in the levels of mRNA Irs1 and Slc2a4 in adipose tissue at the age of 10 weeks, and there are sex differences in the levels of mRNA Irs2 and Pik3cd in the liver, in the levels mRNA Pik3cd and Slc2a4 in the muscle, in the levels mRNA Insr and Pik3cd in adipose tissue at the age of 30 weeks. In young animals, the expression of the genes was higher in females than in males in all tissues. In adult animals, the expression of the genes in the liver was higher in females than in males, the expression of the genes in muscle and adipose tissues were lower in females than in males. In males, the levels of mRNA Insr in the liver and muscles and mRNA Pik3cd in adipose tissue decreased with age, and the level of mRNA Pik3cd in muscles  increased with age. In females, the levels of mRNA Irs1 in muscle and mRNA Pik3cd and Slc2a4 in adipose tissue decreased with age. Thus the molecular basis of sex differences and age-related changes in insulin sensitivity may be a change in expressions of insulin signal transduction genes in the target tissues.